Sponge capable of increasing negative ion release amount

By attaching negative ion coatings to the sponge substrate and using tourmaline composite powder and other materials, the problem of insufficient negative ion release is solved, and the high-efficiency negative ion release and antibacterial performance of the sponge is improved, and the air purification effect is improved.

CN119286054APending Publication Date: 2025-01-10WEIJIANYE (SUZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411416425.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing negative ion release materials have the problem of insufficient negative ion release, making it difficult to effectively purify the air and improve the breathing environment.

Method used

Using negative ion generation coatings, including water-based polyurethane, tourmaline composite powder and rare earth powder, by attaching them to the sponge substrate, using materials such as amination chitosan, modified titanium dioxide and activated carbon in tourmaline composite powder to improve the Negative ion release and antibacterial properties.

Benefits of technology

It significantly improves the negative ion release amount and antibacterial properties of the sponge, so that it can release negative ions in a long and effective manner, improves the air purification effect and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079581170000081
    Figure BDA0005079581170000081
  • Figure BDA0005079581170000091
    Figure BDA0005079581170000091
Patent Text Reader

Abstract

The invention relates to a sponge capable of increasing the negative ion release amount, which comprises a sponge base material and a negative ion generating material, and the negative ion generating material is obtained by attaching a negative ion generating coating to a sponge base material body, the negative ion generation coating comprises the following components in parts by mass: 200-400 parts of waterborne polyurethane, 19-29 parts of tourmaline composite powder, 4-12 parts of rare earth mineral powder and 20-36 parts of a hydrophobic finishing agent, the tourmaline composite powder comprises chitosan, modified titanium dioxide, tourmaline powder and activated carbon. The sponge has the effect of improving the negative ion release effect of the sponge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sponges, and in particular to a sponge capable of increasing the amount of negative ions released. Background Art

[0002] Sponge has a porous structure and can absorb water, insulate sound, and prevent shock, and can be used to clean items.

[0003] As people's requirements for the quality of living environment increase, the development of sponge materials with air purification functions, especially those that can release negative ions, has become a new research direction. Negative ions help purify the air, improve the breathing environment, and have a positive impact on human health.

[0004] However, the current negative ion releasing materials all have the problem of negative ion releasing amount, so there is room for improvement. Summary of the invention

[0005] In order to increase the amount of negative ions released by a sponge, the present application provides a sponge with increased negative ion release.

[0006] The present application provides a sponge with a negative ion release capacity using the following technical solution: A sponge for increasing the amount of negative ion release comprises a sponge substrate and a negative ion generating material. The negative ion generating material is obtained by attaching a negative ion generating coating to a sponge substrate body. The negative ion generating coating comprises the following components in parts by mass: 200-400 parts of waterborne polyurethane, 19-29 parts of tourmaline composite powder, 4-12 parts of rare earth mineral powder, and 20-36 parts of a hydrophobic finishing agent. The tourmaline composite powder comprises chitosan, modified titanium dioxide, tourmaline powder, and activated carbon.

[0007] By adopting the above technical scheme, after the negative ion generating coating is attached to the sponge substrate, the sponge substrate is formed to obtain a negative ion generating material. The tourmaline composite powder in the negative ion generating material can release negative ions, so that the sponge has a negative ion effect. At the same time, the tourmaline composite powder includes chitosan, modified titanium dioxide, tourmaline powder and activated carbon. Aminated chitosan is a natural polymer material with good adsorption and antibacterial properties. Titanium dioxide can also have good antibacterial properties. Activated carbon has good adsorption and antibacterial properties. Sponges usually need to absorb water during use, and bacteria are easily generated in the pore structure. Under the synergistic effect of aminated chitosan, modified titanium dioxide and activated carbon, they can play a synergistic antibacterial role, thereby enhancing the effect of inhibiting bacterial growth.

[0008] Preferably, the tourmaline composite powder is prepared by the following method: The activated carbon is mixed with potassium permanganate solution, and the mixture is allowed to stand and then filtered and dried to obtain the treated activated carbon; chitosan, acetic acid and water are mixed, and the mixture is allowed to stand and then epichlorohydrin is added for cross-linking, and the mixture is centrifuged and filtered after reaction, and dried to obtain prefabricated chitosan; the prefabricated chitosan, water and an amine are mixed to obtain aminated chitosan; the treated activated carbon, aminated chitosan, tourmaline powder and modified titanium dioxide are mixed with water, and the mixture is stirred, glutaraldehyde is added for reaction, and then the mixture is washed, dried and ground to obtain tourmaline composite powder.

[0009] By adopting the above technical scheme, activated carbon, chitosan, negative ion powder and modified nano titanium dioxide are used as raw materials, the activated carbon is treated with potassium permanganate, and the chitosan is cross-linked with epichlorohydrin to obtain aminated chitosan. After the components are mixed, a tourmaline composite powder is obtained. The prepared tourmaline composite powder has porous tree holes and a microporous structure, and the overall compatibility of the system is improved. At the same time, it can better combine with the sponge matrix, thereby improving the stability of the tourmaline composite powder.

[0010] Preferably, the amine includes any one of tetraethylenetriamine and tetraethylenepentamine.

[0011] By adopting the above technical solution, the aminated chitosan has good compatibility and can be more tightly combined with various components in the system, thereby improving the stability of the prepared tourmaline composite powder.

[0012] Preferably, the mass ratio of the activated carbon, aminated chitosan, modified titanium dioxide and tourmaline powder is 1:0.8:1.25:(0.4-0.6).

[0013] By adopting the above technical solution, preferably the mass ratio of activated carbon, aminated chitosan, modified titanium dioxide and tourmaline powder is within the above range, which can improve the stability of the prepared tourmaline composite powder.

[0014] Preferably, the modified titanium dioxide comprises a titanate coupling agent and titanium dioxide.

[0015] Preferably, the modified titanium dioxide is prepared by the following method: The nano-titanium dioxide, water and anhydrous ethanol are mixed, ultrasonically dispersed, and then a titanate coupling agent is added. The mixture is heated for reaction and then centrifuged. After precipitation, the mixture is washed and dried to obtain modified titanium dioxide.

[0016] By adopting the above technical solution, the nano titanium dioxide modified with titanate can be dispersed more evenly in the system, reducing the agglomeration of nano titanium dioxide powder, thereby improving the stability of tourmaline composite powder. At the same time, the modified nano titanium dioxide has good hydrophobic properties, which can improve the water resistance of the negative ion generating material, so that the sponge has a long-lasting negative ion effect.

[0017] Preferably, the mass ratio between the titanate coupling agent and titanium dioxide is (0.07-0.09):1.

[0018] By adopting the above technical solution, preferably the mass ratio between the titanate coupling agent and the titanium dioxide is within the above range, which can effectively improve the stability of the modified titanium dioxide.

[0019] Preferably, the hydrophobic finishing agent comprises vinyl polyhedral oligomeric silsesquioxane, trifluoroethyl methacrylate, and sodium hypochlorite.

[0020] Preferably, the hydrophobic finishing agent is prepared by the following method: Methylpropionamide, trifluoroethyl methacrylate, trimethylsilyl cage-shaped polysilsesquioxane, hydroxyethyl methacrylate, azobisisobutyronitrile and N,N-dimethylformamide are mixed, and stirred to react in an oil bath under a nitrogen atmosphere. The reactant is precipitated and then dried to obtain a hydrophobic reagent.

[0021] By adopting the above technical scheme, vinyl polyhedral polysilsesquioxane and halogenamine compounds are used as raw materials, and sodium hypochlorite is added to prepare a hydrophobic finishing agent. At the same time, the hydrophobic finishing agent has antibacterial properties. After being combined with the sponge substrate, it can effectively improve the overall hydrophobic properties of the sponge substrate, and play a role in air permeability and antibacterial, thereby improving the service life of the sponge.

[0022] Preferably, the negative ion generating coating is prepared by the following method: The water-based polyurethane, tourmaline composite powder, rare earth mineral powder and hydrophobic finishing agent are mixed and stirred to obtain a negative ion generating coating.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The negative ion generating coating is attached to the sponge substrate, and the negative ion generating material is formed on the surface of the sponge substrate. The tourmaline composite powder and rare earth mineral in the negative ion generating material can generate and release negative ions, so that the sponge substrate has the function of releasing negative ions. The tourmaline composite powder includes aminated chitosan, modified titanium dioxide, tourmaline powder and activated carbon, which can effectively improve the antibacterial property of the negative ion generating material, and at the same time improve the compatibility of the negative ion generating material, so that it can be more stably combined with the sponge substrate, thereby improving the negative ion release performance of the sponge; 2. Modified titanium dioxide is prepared by titanate coupling agent. The modified titanium dioxide has good surface energy, so that nano-titanium dioxide can be distributed more evenly in the system, reducing the agglomeration phenomenon, thereby effectively improving the stability of the prepared negative ion release material; 3. A hydrophobic finishing agent is prepared by using halamine compounds, vinyl polyhedral polysilsesquioxane and sodium hypochlorite, thereby improving the overall water wash resistance of the negative ion releasing material, thereby improving the stability of the negative ion releasing material, and enabling the negative ion releasing material to release negative ions for a long time. At the same time, the prepared hydrophobic finishing agent has good antibacterial properties, which can further improve the antibacterial properties of the sponge. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained from commercial sources.

[0025] Example 1 Preparation of modified titanium dioxide: 20 g of nano titanium dioxide, 70 g of deionized water and 560 g of anhydrous ethanol were mixed, and after ultrasonic dispersion for 1 hour, 1.4 g of titanate coupling agent (CAS No.: 103432-54-8) was added, and the pH value of the system was adjusted to 4 with acetic acid. The mixture was heated to 80°C and reacted for 4 hours, and then centrifuged. After precipitation, the mixture was washed alternately with ethanol and deionized water three times. After washing, the precipitate was dried in an oven at 80°C for 10 hours to obtain modified titanium dioxide.

[0026] Preparation of tourmaline composite powder: 11.59 g of activated carbon was mixed with 0.1 mol / L and 50 g of potassium permanganate solution, allowed to stand for 12 h, filtered, and dried in an oven at 80 ° C for 8 h to obtain treated activated carbon; 30 g of chitosan (CAS No.: 9012-76-4), 3 g of acetic acid and 300 g of deionized water were mixed, allowed to stand for 4 h, 18 g of epichlorohydrin was added for cross-linking, 0.1 mol / L sodium hydroxide solution was used to adjust the pH value of the system to 12, reacted at 70 ° C for 6 h, filtered after centrifugation, and dried to obtain prefabricated chitosan, and the prefabricated chitosan, 300 g of deionized water was mixed with 18 g of amine, and the pH value was adjusted to 10 with sodium hydroxide, and the mixture was reacted at a slow temperature of 60 ° C for 4 hours to obtain aminated chitosan; the treated activated carbon, 9.28 g of aminated chitosan, 4.64 g of tourmaline powder, 14.49 g of modified titanium dioxide and 300 g of distilled water were mixed, stirred at a speed of 300 r / min for 30 minutes, 50 g of glutaraldehyde was added, and the mixture was reacted at 40 ° C for 6 hours, then washed with deionized water, and then dried in an oven at 60 ° C for 8 hours, and the tourmaline composite powder was obtained after grinding.

[0027] Wherein, the amine is triethylenetetramine (CAS No.: 112-24-3).

[0028] Preparation of hydrophobic finishing agent: 4 g of methacrylamide (CAS No.: 79-39-0), 22 g of trifluoroethyl methacrylate (CAS No.: 352-87-4), 2.5 g of trimethylsilyl cage-shaped polysilsesquioxane (CAS No.: 51777-38-9), 3 g of hydroxyethyl methacrylate (CAS No.: 868-77-9), 4 g of azobisisobutyronitrile (CAS No.: 78-67-1) and 60 g of N,N-dimethylformamide (CAS No.: 68-12-2) were mixed and heated at 65 °C. Under the condition of an oil bath, in an atmosphere of nitrogen protection, the stirring speed is maintained at 450r / min, the stirring reaction is carried out for 9 hours, and deionized water is used to precipitate after the reaction, and then it is dried in an oven at 50°C for 24 hours to obtain a hydrophobic copolymer; 5g of the hydrophobic copolymer, 0.6g of sodium dodecylbenzene sulfonate (CAS No.: 25155-30-0), 3g of hexamethylene diisocyanate (CAS No.: 822-06-0) and 50g of deionized water are mixed, 20g of sodium hypochlorite is added, and the hydrophobic finishing agent is obtained after stirring.

[0029] Preparation of negative ion generating coating: 200 g of waterborne polyurethane, 19 g of tourmaline composite powder, 4 g of rare earth mineral powder, and 20 g of a hydrophobic finishing agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a negative ion generating coating.

[0030] Preparation of negative ion releasing sponge: The sponge substrate was dried at 40 degrees Celsius for 3 hours to obtain a pretreated sponge substrate; the pretreated sponge substrate was completely immersed in the negative ion generating coating, stirred at a speed of 200 r / min for 1.5 hours, the sponge substrate was removed, and allowed to stand for 3 hours. After washing with deionized water, it was dried in an oven at 45 degrees Celsius for 1 hour, so that the negative ion material adhered to the sponge substrate to obtain a negative ion releasing sponge.

[0031] Example 2 Preparation of modified titanium dioxide: 20 g of nano titanium dioxide, 70 g of deionized water and 560 g of anhydrous ethanol were mixed, and after ultrasonic dispersion for 1 hour, 1.8 g of titanate coupling agent was added, and the pH value of the system was adjusted to 4 with acetic acid. The temperature was raised to 80°C and reacted for 4 hours, and then centrifuged. After precipitation, ethanol and deionized water were used to wash alternately three times. After washing, the precipitate was dried in an oven at 80°C for 10 hours to obtain modified titanium dioxide.

[0032] Preparation of tourmaline composite powder: 10.96 g of activated carbon was mixed with 0.1 mol / L and 50 g of potassium permanganate solution, allowed to stand for 12 h, filtered, and dried in an oven at 80 ° C for 8 h to obtain treated activated carbon; 30 g of chitosan, 3 g of acetic acid, and 300 g of deionized water were mixed, allowed to stand for 4 h, 18 g of epichlorohydrin was added for cross-linking, 0.1 mol / L sodium hydroxide solution was used to adjust the pH value of the system to 12, the reaction was carried out at 70 ° C for 6 h, the mixture was filtered after centrifugation, and the prefabricated chitosan was obtained. The prefabricated chitosan and 300 g of deionized water were mixed. Water is mixed with 20g of amine, and the pH value is adjusted to 10 with sodium hydroxide, and the reaction is carried out at a slow temperature of 60°C for 4h to obtain aminated chitosan; the treated activated carbon, 8.77g of aminated chitosan, 6.57g of tourmaline powder, 13.70g of modified titanium dioxide and 300g of distilled water are mixed, stirred at a speed of 300r / min for 30min, 50g of glutaraldehyde is added, and the reaction is carried out at 40°C for 6h, and then washed with deionized water, and then dried in an oven at 60°C for 8h, and the tourmaline composite powder is obtained after grinding.

[0033] Wherein, the amine is tetraethylenepentamine (CAS No.: 112-57-2).

[0034] Preparation of hydrophobic finishing agent: 4 g of methacrylamide, 22 g of trifluoroethyl methacrylate, 2.5 g of trimethylsilyl cage polysilsesquioxane, 3 g of hydroxyethyl methacrylate, 4 g of azobisisobutyronitrile and 60 g of N,N-dimethylformamide were mixed, and the mixture was stirred at 65° C. in an oil bath under a nitrogen atmosphere at a speed of 450 r / min for 9 hours. After the reaction, deionized water was used for precipitation, and then the mixture was dried in an oven at 50° C. for 24 hours to obtain a hydrophobic copolymer. 5 g of the hydrophobic copolymer, 0.6 g of sodium dodecylbenzene sulfonate, 3 g of hexamethylene diisocyanate and 50 g of deionized water were mixed, and 20 g of sodium hypochlorite was added, and the mixture was stirred to obtain a hydrophobic finishing agent.

[0035] Preparation of negative ion generating coating: 400 g of waterborne polyurethane, 29 g of tourmaline composite powder, 12 g of rare earth mineral powder, and 36 g of a hydrophobic finishing agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a negative ion generating coating.

[0036] Preparation of negative ion releasing sponge: The sponge substrate was dried at 40 degrees Celsius for 3 hours to obtain a pretreated sponge substrate; the pretreated sponge substrate was completely immersed in the negative ion generating coating, stirred at a speed of 200 r / min for 1.5 hours, the sponge substrate was removed, and allowed to stand for 3 hours. After washing with deionized water, it was dried in an oven at 45 degrees Celsius for 1 hour, so that the negative ion material adhered to the sponge substrate to obtain a negative ion releasing sponge.

[0037] Example 3 Preparation of modified titanium dioxide: 20 g of nano titanium dioxide, 70 g of deionized water and 560 g of anhydrous ethanol were mixed, and after ultrasonic dispersion for 1 hour, 1.6 g of titanate coupling agent was added, and the pH value of the system was adjusted to 4 with acetic acid. The temperature was raised to 80°C and reacted for 4 hours, and then centrifuged. After precipitation, ethanol and deionized water were used to wash alternately three times. After washing, the precipitate was dried in an oven at 80°C for 10 hours to obtain modified titanium dioxide.

[0038] Preparation of tourmaline composite powder: 11.27 g of activated carbon was mixed with 0.1 mol / L and 50 g of potassium permanganate solution, allowed to stand for 12 h, filtered, and dried in an oven at 80 ° C for 8 h to obtain treated activated carbon; 30 g of chitosan, 3 g of acetic acid, and 300 g of deionized water were mixed, allowed to stand for 4 h, 18 g of epichlorohydrin was added for cross-linking, 0.1 mol / L sodium hydroxide solution was used to adjust the pH value of the system to 12, the reaction was carried out at 70 ° C for 6 h, the mixture was filtered after centrifugation, and the prefabricated chitosan was obtained. The prefabricated chitosan and 300 g of deionized water were mixed. Water is mixed with 18g of amine, and the pH value is adjusted to 10 with sodium hydroxide, and the reaction is carried out at a slow temperature of 60°C for 4h to obtain aminated chitosan; the treated activated carbon, 9.01g of aminated chitosan, 5.63g of tourmaline powder, 14.09g of modified titanium dioxide and 300g of distilled water are mixed, stirred at a speed of 300r / min for 30min, 50g of glutaraldehyde is added, and the reaction is carried out at 40°C for 6h, and then washed with deionized water, and then dried in an oven at 60°C for 8h, and the tourmaline composite powder is obtained after grinding.

[0039] Wherein, the amine is tetraethylenetriamine.

[0040] Preparation of hydrophobic finishing agent: 4 g of methacrylamide, 22 g of trifluoroethyl methacrylate, 2.5 g of trimethylsilyl cage polysilsesquioxane, 3 g of hydroxyethyl methacrylate, 4 g of azobisisobutyronitrile and 60 g of N,N-dimethylformamide were mixed, and the mixture was stirred at 65° C. in an oil bath under a nitrogen atmosphere at a speed of 450 r / min for 9 hours. After the reaction, deionized water was used for precipitation, and then the mixture was dried in an oven at 50° C. for 24 hours to obtain a hydrophobic copolymer. 5 g of the hydrophobic copolymer, 0.6 g of sodium dodecylbenzene sulfonate, 3 g of hexamethylene diisocyanate and 50 g of deionized water were mixed, and 20 g of sodium hypochlorite was added, and the mixture was stirred to obtain a hydrophobic finishing agent.

[0041] Preparation of negative ion generating coating: 300 g of waterborne polyurethane, 24 g of tourmaline composite powder, 8 g of rare earth mineral powder, and 28 g of a hydrophobic finishing agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a negative ion generating coating.

[0042] Preparation of negative ion releasing sponge: The sponge substrate was dried at 40 degrees Celsius for 3 hours to obtain a pretreated sponge substrate; the pretreated sponge substrate was completely immersed in the negative ion generating coating, stirred at a speed of 200 r / min for 1.5 hours, the sponge substrate was removed, and allowed to stand for 3 hours. After washing with deionized water, it was dried in an oven at 45 degrees Celsius for 1 hour, so that the negative ion material adhered to the sponge substrate to obtain a negative ion releasing sponge.

[0043] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, 0.8 g of titanate coupling agent is used when preparing modified titanium dioxide.

[0044] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, 2.4 g of titanate coupling agent is used when preparing modified titanium dioxide.

[0045] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the tourmaline composite powder, 12.31 g of activated carbon, 9.85 g of aminated chitosan, 15.39 g of modified titanium dioxide and 2.45 g of tourmaline powder are used.

[0046] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the tourmaline composite powder, 10.39 g of activated carbon, 8.31 g of aminated chitosan, 12.99 g of modified titanium dioxide, and 8.31 g of tourmaline powder are used.

[0047] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing tourmaline composite powder, the modified titanium dioxide is replaced by ordinary nano titanium dioxide.

[0048] Example 9 Example 9 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 9, when preparing the tourmaline composite powder, the aminated chitosan is replaced by ordinary chitosan.

[0049] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, no trimethylsilyl cage-shaped polysilsesquioxane is added when preparing the hydrophobic finishing agent.

[0050] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, trifluoroethyl methacrylate is not added when preparing the hydrophobic finishing agent.

[0051] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the hydrophobic finishing agent, sodium hypochlorite is replaced with an equal amount of deionized water.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, no activated carbon is added when preparing the tourmaline composite powder.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 3. In Comparative Example 2, no modified titanium dioxide is added when preparing the tourmaline composite powder.

[0054] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the tourmaline composite powder is replaced with ordinary tourmaline powder.

[0055] Performance testing The following performance tests were performed on the samples of Examples 1-2 and Comparative Examples 1-3: (1) Negative ion release test Using GB / T 30128-2013 as the test standard, the negative ion release of the sample was tested. Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1.

[0056] (2) Washability test The samples were washed with running water at 40℃±1℃ and kept for 8h. The negative ion release of the samples was then retested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0057] (3) Antibacterial performance test According to GB / T 20944.1, the antibacterial performance of the samples was tested. The antibacterial rate was tested after 7 days. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.

[0058] Data analysis Combined with Table 1, it can be seen that the negative ion release of Examples 1-3 is 2117 / cm 3 The above indicates that the sponge prepared by the present application has excellent negative ion release performance; the negative ion release amount of Examples 1-3 after washing is 1547 / cm 3And above, it shows that the negative sponge prepared by the present application has good hydrophobic properties, thereby playing a role of water-resistant, making the release of negative ions more lasting and stable; the antibacterial rates of Escherichia coli in Examples 1-3 are all 99.7% and above, and the antibacterial rates of Staphylococcus aureus are all 99.7% and above, indicating that the sponge prepared by the present application has good antibacterial properties.

[0059] In Example 4 and Example 5, when preparing modified titanium dioxide, the mass ratio between nano titanium dioxide and titanate coupling agent is not within the range specified in the present application. When the content of titanate coupling agent is too little, the surface energy improvement effect of nano titanium dioxide is difficult to be further improved, so nano titanium dioxide agglomerates in the system, thereby affecting the overall stability of the tourmaline composite powder and reducing the bonding performance with the sponge substrate; when the amount of titanate coupling agent added is too much, the particle size uniformity of nano titanium dioxide is affected, thereby reducing the stability and hydrophobic properties of nano titanium dioxide.

[0060] In Example 6 and Example 7, when preparing tourmaline composite powder, the mass ratios of activated carbon, aminated chitosan, modified titanium dioxide and tourmaline powder are not within the range specified in the present application. When the content of tourmaline powder is too much, due to the smooth surface and uneven particle size of the tourmaline powder, agglomeration occurs in the system, affecting the overall stability of the system; when the content of tourmaline powder is too little, the amount of negative ions released is too little, and it is difficult to improve the negative ion release performance of the sponge.

[0061] In Example 8, when preparing tourmaline composite powder, the modified titanium dioxide is replaced by ordinary titanium dioxide. The surface energy of the unmodified titanium dioxide is difficult to improve, and agglomeration occurs in the system, affecting the overall stability of the system, so that various performances are reduced.

[0062] In Example 9, when preparing tourmaline composite powder, aminated chitosan is replaced with ordinary chitosan. The compatibility of unmodified chitosan is reduced, and the combination effect with each component is difficult to be further improved, thereby reducing the stability of the components.

[0063] In Example 10, when preparing the hydrophobic finishing agent, trimethylsilyl cage-shaped polysilsesquioxane was not added, the silicon content in the hydrophobic finishing agent decreased, the roughness of the system decreased, it was difficult to adhere to the surface of the sponge substrate more stably, and the hydrophobic performance was also reduced.

[0064] In Example 11, when preparing the hydrophobic finishing agent, trifluoroethyl methacrylate was not added, and the fluorine element in the system decreased, making it difficult to further improve the hydrophobic performance of the system.

[0065] In Example 12, when preparing the hydrophobic finishing agent, it was difficult to improve the roughness of the sponge substrate surface without adding sodium hypochlorite, and the antibacterial performance was reduced.

[0066] In Comparative Example 1, no activated carbon was added when preparing the tourmaline composite powder, which made it difficult to further improve the antibacterial performance of the system. At the same time, the cross-linking degree of the tourmaline composite powder system was affected, and the stability was reduced.

[0067] In Comparative Example 2, when preparing the tourmaline composite powder, no modified titanium dioxide was added. Failure to add modified titanium dioxide affected the hydrophobicity of the system, and the antibacterial performance was difficult to be further improved.

[0068] In Comparative Example 3, the tourmaline composite powder was replaced with ordinary tourmaline powder. The surface energy of the untreated tourmaline composite powder was difficult to be further improved, and the tourmaline powder agglomerated in the system, affecting the overall stability of the system. At the same time, the hydrophobicity and antibacterial properties were also difficult to be further improved.

[0069] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A sponge for increasing the amount of negative ion release, characterized in that: It includes a sponge substrate and a negative ion generating material. The negative ion generating material is obtained by attaching a negative ion generating coating to a sponge substrate body. The negative ion generating coating includes the following components in parts by weight: 200-400 parts of waterborne polyurethane, 19-29 parts of tourmaline composite powder, 4-12 parts of rare earth mineral powder, and 20-36 parts of hydrophobic finishing agent; the tourmaline composite powder comprises chitosan, modified titanium dioxide, tourmaline powder and activated carbon.

2. A sponge for increasing the amount of negative ion release according to claim 1, characterized in that: The tourmaline composite powder is prepared by the following method: The activated carbon is mixed with potassium permanganate solution, and the mixture is allowed to stand and then filtered and dried to obtain the treated activated carbon; chitosan, acetic acid and water are mixed, and the mixture is allowed to stand and then epichlorohydrin is added for cross-linking, and the mixture is centrifuged and filtered after reaction, and dried to obtain prefabricated chitosan; the prefabricated chitosan, water and an amine are mixed to obtain aminated chitosan; the treated activated carbon, aminated chitosan, tourmaline powder and modified titanium dioxide are mixed with water, and the mixture is stirred, glutaraldehyde is added for reaction, and then the mixture is washed, dried and ground to obtain tourmaline composite powder.

3. A sponge for increasing the amount of negative ion release according to claim 2, characterized in that: The amine compound includes any one of tetraethylenetriamine and tetraethylenepentamine.

4. A sponge for increasing the amount of negative ion release according to claim 2, characterized in that: The mass ratio of the activated carbon, aminated chitosan, modified titanium dioxide and tourmaline powder is 1:0.8:1.25:(0.4-0.6).

5. A sponge for increasing the amount of negative ion release according to claim 1, characterized in that: The modified titanium dioxide comprises a titanate coupling agent and titanium dioxide.

6. A sponge for increasing the amount of negative ion release according to claim 5, characterized in that: The modified titanium dioxide is prepared by the following method: The nano-titanium dioxide, water and anhydrous ethanol are mixed, ultrasonically dispersed, and then a titanate coupling agent is added. The mixture is heated for reaction and then centrifuged. After precipitation, the mixture is washed and dried to obtain modified titanium dioxide.

7. A sponge for increasing the amount of negative ion release according to claim 5, characterized in that: The mass ratio between the titanate coupling agent and titanium dioxide is (0.07-0.09):

1.

8. A sponge for increasing the amount of negative ion release according to claim 1, characterized in that: The hydrophobic finishing agent includes vinyl polyhedral oligomeric silsesquioxane, trifluoroethyl methacrylate and sodium hypochlorite.

9. A sponge for increasing the amount of negative ion release according to claim 8, characterized in that: The hydrophobic finishing agent is prepared by the following method: Methylpropionamide, trifluoroethyl methacrylate, trimethylsilyl cage-shaped polysilsesquioxane, hydroxyethyl methacrylate, azobisisobutyronitrile and N,N-dimethylformamide are mixed, and stirred to react in an oil bath under a nitrogen atmosphere. The reactant is precipitated and then dried to obtain a hydrophobic reagent.

10. A sponge for increasing the amount of negative ion release according to claim 1, characterized in that: The negative ion generating coating is prepared by the following method: The water-based polyurethane, tourmaline composite powder, rare earth mineral powder and hydrophobic finishing agent are mixed and stirred to obtain a negative ion generating coating.

Citation Information

Cited By

  • Healthy herbal particle art coating

    CN119752259A

  • Nanometer type multifunctional negative ion material and preparation method thereof

    CN121488974A